A metamodelling approach to configuration knowledge representation. (21st December 2010) - Asikainen, Timo; Mannisto, Tomi
Traditionally, product configuration research has focused on two main areas: first, encoding configuration knowledge in terms of a knowledge representation language, such as a form of constraint satisfaction or some description logic, and reasoning about the properties of the encoding; second, implementing practical configuration systems. Less attention has been given to the conceptual and semantic foundations of product configuration. In this paper, we apply recent results in metamodelling, in particular the metamodelling language NIVEL, to product configuration. In more detail, we show how NIVEL can be used to explicitly represent knowledge on three levels of abstraction, e.g., configuration modelling concepts, configuration models and their instances, configurations. Major parts of the semantics for configuration modelling languages can be obtained as a by-product of defining them using NIVEL. Finally, just as for configurations, well-formedness constraints on configuration models can be expressed declaratively.